Greenwashing and board effectiveness: Moderating role of CSR committee from Malaysia evidence - Jamil, Nurul Nazlia; Wahyuni, Ersa Tri (Edelweiss Applied Science and Technology, 2025)
Greenwashing comes in many forms from misleading claims and ambiguous terms to using nature imagery to suggest sustainability. As ESG obligations and transparency demands grow, so does the scrutiny around greenwashing. The purpose of the study is to examine the role of board effectiveness (diversity, independence, size and expertise) on greenwashing with the role of CSR committee as the moderator in the Malaysian listed companies. This paper analyzes data from the year 2021-2023 with a sample of 1068 firm year observations. The regression analyses have been conducted and the result highlighted that the board effectiveness (diversity, independence, size and expertise) negatively related with the greenwashing behaviour in Malaysian listed companies. Furthermore, the CSR role has shown negatively moderate the relationship between board effectiveness and greenwashing relationship. The results imply that the synergy from the effective board of directors able to curb greenwashing behaviour in the companies. This study goes beyond only offering greenwashing; instead, it offers some policy implications for businesses to be sustainable.